An isolated, occult non-union fibular shaft fracture in an athlete, diagnosed by portable ultrasound screening. (July 2015) - Inklebarger, James; Clarke, T. P.
<x content-type="archive" xml:space="preserve">Abstract</x> Isolated fibular shaft fractures (IFSF) have rarely been described in the literature. As the fibula is a non weight-bearing bone, fractures may present subtly as a soft tissue injury or in some cases be completely asymptomatic. Though usually self limiting, missed IFSF may progress to non-union with potential poor healing outcomes, particularly in those engaged in continued rigorous athletic activity. This is a case of occult IFSF, initially identified via diagnostic ultrasound (DU) circa one year post onset of lower limb pain with impact activity. X-ray confirmed bony non-union. Open reduction internal fixation (ORIF) was performed, with bone biopsy negative for pathological fracuture. Union was achieved, but symptoms of allodynia and hyperesthesia persisted post metalwork removal one year post surgery. The patient was unable to return to recreational sporting activity and referred for pain control team management.